Prefrontal cortex and executive function in young children: a review of NIRS studies - Moriguchi, Yusuke; Hiraki, Kazuo (Frontiers in Human Neuroscience, 2013)
Executive function refers to the higher-order cognitive control process for the attainment of a specific goal. There are several subcomponents of executive function, such as inhibition, cognitive shifting, and working memory. Extensive neuroimaging research in adults has revealed that the lateral prefrontal cortex plays an important role in executive function. Developmental studies have reported behavioral evidence showing that executive function changes significantly during preschool years. However, the neural mechanism of executive function in young children is still unclear. This article reviews recent near-infrared spectroscopy (NIRS) research that examined the relationship between the development of executive function and the lateral prefrontal cortex. Specifically, this review focuses on cognitive shifting, inhibitory control, and working memory in young children. Research has consistently shown significant prefrontal activation during tasks in typically developed children, but this activation may be abnormal in children with developmental disorders. Finally, methodological issues and future directions are discussed.